Perceptions Among Adolescents In Penang And Kedah Of Their Father's And Mother's Parenting - Ooi, Pei Wen (2012)
Mothers have culturally been seen as the primary caregivers of children while fathers are seen as principal breadwinners. With women’s increased involvement in the labour market especially through working outside of the home, equal distribution of parenting responsibilities between mothers and fathers have become relevant areas of inquiry, especially in the context of the possible problem of “double-burden” for women in the family. Based on a sample of 339 Form Four students from Penang and Kedah, this study investigates how adolescents perceived the parental nurturance and involvement of their mothers and fathers by using 20 domains of parenting.